EFEKTIVITAS METODE PEER LEARNING UNTUK MENINGKATKAN PROSES BELAJAR PADA PEMBELAJARAN DOKKAI (PENELITIAN EKSPERIMEN PADA MAHASISWA ANGKATAN 2017 UNIVERSITAS RIAU) - Fairuz Rifa Ferial; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study discusses the method of improving peer learning to improve the learning process of dokkai in Japanese Language Education class of 2017 at the University of Riau. The purpose of this study is to examine whether the peer learning method is effective to improve the learning process of dokkai. In this research, researchers used a weak experiment design with evidence of no class as a comparison. The technique of collecting data is done by giving a test. Test results on the pretest and posttest had increased, on the pretest the average test score was 64.75 while the post-test rises to 89. The test results are processed using a statistical test called ‘t-test’ manually to acknowledge how significant the impact in student learning outcomes when using peer learning methods. Based on the processing of statistical test data there is the to = 6.2 and tt = 2.10 (significant level of 5%), if to > tt then H0 is declined and Ha is accepted, which means there is a significant effect on the use of peer learning methods to improve the learning process dokkai on Japanese Language Education class of 2017 at Riau University.Key Words: Peer Learning, Dokkai